2019
DOI: 10.1002/slct.201802960
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Graphite Pencil Grades for the Design of Suitable Electrodes for Stacking Multiple Single‐Inlet Paper‐Pencil Fuel Cells

Abstract: We present a single-inlet paper-pencil based microfluidic fuel cell which works on the capillary driven fluid flow of a mixture of fuel (formic acid) and electrolyte (dilute sulfuric acid) solutions as a single entity. Different types of pencils are used to prepare the graphite electrodes to observe their effect on the fuel cell performance. The graphite electrodes are porous and act as a gas diffusion electrode which breaths in oxygen directly from the quiescent air and out CO 2 from the cell. The paper fuel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 44 publications
(47 reference statements)
0
19
0
2
Order By: Relevance
“…The cumulative energy density generated from the device after five cycles are measured as~200 mW after regeneration of the fuel by applying external voltage. [6][7][8][9] Kjeang et al presented a planar MFC using graphite as electrodes to generate an energy density of 35 mW cm −2 at 2 M vanadium concentration. The present self-standing spiral-shaped MFC will eliminate the challenges associated with two inlet membrane-less fuel cells and has the potential to scale up for commercial application in portable energy generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cumulative energy density generated from the device after five cycles are measured as~200 mW after regeneration of the fuel by applying external voltage. [6][7][8][9] Kjeang et al presented a planar MFC using graphite as electrodes to generate an energy density of 35 mW cm −2 at 2 M vanadium concentration. The present self-standing spiral-shaped MFC will eliminate the challenges associated with two inlet membrane-less fuel cells and has the potential to scale up for commercial application in portable energy generation.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,5 Recently, the paper-based MFCs became familiar as capillary-based self-pumping membrane-less fuel cells in energy generation. [6][7][8][9] Kjeang et al presented a planar MFC using graphite as electrodes to generate an energy density of 35 mW cm −2 at 2 M vanadium concentration. 10 In all these studies, the surface area of the electrode and convective-diffusive mass transport play a crucial role in electrochemical reactions in MFCs.…”
Section: Introductionmentioning
confidence: 99%
“…The electrodes were prepared using graphite pencils by creating multiple strokes and placed over the microchannel with appropriate dimensions. 18 As shown in Figure 5, the rectangular graphite electrodes (2.5 cm in length × 0.2 cm in width) were prepared on a cellulose paper along the length of the microchannel. In this arrangement, the active surface area of the electrode of MPFC was 0.5 cm 2 .…”
Section: Mpfc Electrode Fabricationmentioning
confidence: 99%
“…In this context, hereby, a simple and optimized MPFC is presented. Here, formic acid and sulfuric acid act as fuel and electrolyte, respectively, and a combination of the strokes of different graphite pencils was used to fabricate the electrodes . Moreover, cellulose papers of various grades (Gr 6, Gr 3, Gr 41, and Gr 113) have been used as absorbent pads for the improvement of cell performance with Gr 1 paper as microchannel.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the recent researches in the field of paper–pencil based microfuel cells employ manual deposition of graphite on the paper for fabricating the electrode. Arun et al reported formic acid microfluidic fuel cell with manual graphite pencil electrodes with diverse grades of pencils 10 , 11 . Veerubhotla and Ye et al studied performance with graphite pencil stroke electrodes on paper based microbial fuel cells 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%